A Sensitive Sensor for trace Hg2+ Determination Based on Ultrathin g-C3N4 Modified Glassy Carbon Electrode. (20th December 2015) - Zhang, Junling; Zhu, Zengwei; Di, Junwei; Long, Yumei; Li, Weifeng; Tu, Yifeng
Abstract: This work reports a sensitive sensor for the electrochemical determination of trace mercury (Hg 2+ ) by employing ultrathin graphitic carbon nitride (utg-C3 N4 ) nanosheet as enhanced sensing platform. The utg-C3 N4 nanosheets were obtained by exfoliating the bulk g-C3 N4, which was synthesized via a thermal polycondensation process. The as-prepared samples were characterized by x-ray diffraction (XRD), transmission electron microscopy (TEM), fourier transform infrared (FTIR) spectroscopy and atomic force microscopy (AFM), which confirmed graphite-like structure with thickness of about 8 nm. The g-C3 N4 nanosheets can be easily attached on the surface of glassy carbon (GC) electrode free of any film-forming agent. It was found that Utg-C3 N4 modified GC electrode showed enhanced electrochemical response to Hg 2+ in comparison with bulk g-C3 N4, which could be ascribed to the strong affinity between utg-C3 N4 and Hg 2+ through its NH and NH2 groups. This allows detection of Hg 2+ in aqueous solutions with high sensitivity and selectivity. Under the optimized experimental conditions, the anodic stripping voltammetric (ASV) currents are linearly responsible to Hg 2+ concentrations in the range of 0.1–15 μg/L with a detection limit of 0.023 μg/L (S/N = 3). The sensitivity of the as-constructed sensor is about 6.8 μA(μg/L) −1  cm −2 . In addition, the proposed sensor was applied in determining Hg 2+ in practical samples and the results are comparable to those obtained by inductively coupled plasma atomic emission spectrometry (ICP-AES) method.